Factors associated with mortality in HIV patients failing antiretroviral therapy, in Salvador, Brazil - Haguihara,Tatiana (2019)
ABSTRACT Highly active antiretroviral therapy (HAART) has significantly improved survival of people living with HIV/Aids (PLWHA). However, poor treatment adherence to HAART and other problems, still cause therapy failure and contribute to increased morbidity and mortality of PLWHA. In this retrospective cohort study (2013-2015), we sought to evaluate the factors associated with mortality of PLWHA failing HAART in 2013, who were receiving care at a reference center for sexually transmitted diseases (STD) and HIV/AIDS. A total of 165 individuals over 18 years of age who were failing antiretroviral therapy were evaluated. In two-year follow-up, 19 (11.5%) deaths were documented. There were a significant association between mortality and report of illicit drug use (53%, p < 0.01), being attended by a larger number of medical professionals (6.3 ± 3.2, p = 0.02), use of firstline non-nucleoside reverse transcriptase inhibitor (74%, p = 0.01), and history of interrupting HAART ≥3 months (90%), p = 0.02). Patients who died had a significantly higher viral load (mean 49,192.4 ± 35,783.6 copies/mL) than survivors (26,389.2 ± 27,416 copies/mm3, p < 0.01), lower mean CD4 cell counts (127.8 ± 145.6 cells/mm3 vs. 303.3 ± 202.4 cells/mm3, p < 0.01), and higher frequency of previous virologic failure (89% vs. 74.7%, p < 0.01). Our results reinforce the importance of early detection and prevention of virologic failure, to reduce the mortality associated with this event.